Nanocomposite coatings obtained by electrophoretic co-deposition of poly(etheretherketone)/graphene oxide suspensions - Gonzalez-Castillo,EI; Costantini,T; Shaffer,MSP; Boccaccini,AR (Journal of Materials Science, 2020)
Nanocomposite coatings were successfully prepared by electrophoretic deposition of poly(etheretherketone) (PEEK)/graphene oxide (GO) suspensions. The GO flakes developed a large-scale co-continuous morphology with the basal plane mainly aligned with the coating surface. However, the PEEK particles were also found to be wrapped by GO nanosheets when deposited on the stainless steel substrate. Both phenomena, the co-continuous morphology and the wrapping effect, were dependent on the initial GO content in the suspension and influenced the final morphological characteristics of the thermally treated coatings. The PEEK matrix developed a dendritic morphology during its cooling from the molten state because of transcrystallinity that was induced by the incorporation of GO. The preparation of suspensions involved tip ultrasonication (TS) to deagglomerate, disperse, and mill the PEEK particles. A detailed study of the microstructure revealed that TS tended not only to reduce PEEK particle size, but also to promote an elongated shape, favourable for the nanocomposite coatings.